Arts-Based Methods in Education Around the World. - Du, Xiangyun. (River Publishers, 2018)
In this extraordinary collection, contributions are collected from experts all over the world and involve a multiplicity of arts genres and traditions. They are informative on specific topics, but also offer a clear monitoring of the ways in which the general attention to the arts in education evolves through time.